Structural and Physicochemical Properties of Starch from Non-waxy and Waxy Proso Millets - CHANG Lei, LI Xinyi, YAO Yang, LI Mengqing, NIU Ruimiao, DU Shuangkui (Shipin Kexue, 2025)
Proso millet starch from two waxy proso millet cultivars (‘Shaanmi 3’ and ‘Shaanmi 5’) and two non-waxy proso millet cultivars (‘Shaanmi 4’ and ‘Shaanmi 6’) was extracted using the wet-milling method and analyzed for structural and physicochemical properties. The results showed that all four kinds of proso millet starch exhibited polygonal or spherical granules; their crystal structure was type A and their Fourier transform infrared (FTIR) spectra were similar to one another. The crystallinity, short-range ordered degree, peak viscosity, breakdown, gelatinization temperature, and enthalpy of waxy proso millet starch were significantly higher than those of non-waxy proso millet starch (P < 0.05), whereas the pasting temperature, final viscosity, setback, and retrogradation rate of waxy proso millet starch were substantially lower than those of non-waxy proso millet starch (P < 0.05). Proso millet starch paste exhibited pseudoplastic non-Newtonian fluid characteristics and thixotropy. Non-waxy proso millet starch pastes showed higher shear-thinning degree and gel strength, while waxy proso millet starch pastes displayed higher pseudoplasticity and thixotropy. Compared with waxy proso millet starch, non-waxy proso millet starch possessed lower rapidly digestible starch content and higher resistant starch content, indicating higher resistance to digestion. The physicochemical properties of proso millet starch were significantly affected by its amylose content and structure.